Social criticism and memory in the poetry of María Mercedes Carranza - Basauri Mata, Karen Lucero (2022)
This article will analyze poems from the books Vainas y otros poemas (1972), Tengo miedo (1983) and El canto de las moscas (versión de los acontecimientos) (1998), by the Colombian author María Mercedes Carranza (1945-2003), in order to establish the two main threads in her poetry: the purification of language and social criticism. We understand the first as an abandonment of the previous language and style, poetry of tinsel, for a poetry that returns to the word the possibility of meaning, a return to the colloquial and everyday that reflects the national reality. Therefore, the poet dares to say everything that has been ignored and, through her verses, exposes the corruption and violence that afflict Colombia.